Efektivitas Konsep Restorative Justice Dalam Penanganan Kasus Penganiayaan Oleh Kejaksaan Negeri Bone Bolango - Ilham Saputra Machmud; Dian Ekawaty Ismail; Jufryanto Puluhulawa (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The existence of criminal cases arises because there are criminal acts handled by law enforcement. Criminal cases always arise whenever there is a criminal process. Criminal acts or crimes are an inseparable part of life in society. The public measures justice not by the word for word formulation of the law, but by what is felt and seen by the decisions issued based on the legal reality witnessed. The aim of this research is to examine the role of prosecutors in resolving cases using a restorative justice approach. To find out the factors that hinder prosecutors in resolving cases using the concept of restorative justice. In this research, researchers used Empirical Law research. And the data feeding technique is carried out using the interview technique. The data obtained by researchers in this study used quantitative and qualitative methods. The results of the research show that the resolution of acts of abuse by the Bone Bolango District Prosecutor's Office through a restorative justice approach has been adopted. The inhibiting factors experienced by the Bone Bolango prosecutor's office were legal factors, human resources, clashes between victims and perpetrators and community culture.